Turbulent heat transfer in pipes with increased roughness through shavings of helical ribs. (15th August 2023) - Kügele, Simon; Mathlouthi, Gino Omar; Renze, Peter; Dietl, Jochen; Grützner, Thomas
Abstract: Large-eddy simulations of mircrostructured pipes are carried out in this study. The pipes are helically ribbed with several starts from which shavings are cut out along the rib. A Reynolds number of 16, 000 and a Prandtl number of 9 are applied. Cyclic boundary conditions are used to simulate an infinitely long pipe and a LES turbulence model is applied. The results show that both the number of starts and the distance of the shavings along the rib, have an impact on turbulence and heat transfer. An optimum was found for the number of starts regarding heat transfer. The heat transfer area increases for a higher number of starts, but the flow-related heat transfer decreases. Thus, an optimal arrangement of starts was identified for this pipe configuration. The variation of the arrangement showed that the pressure loss can be reduced by an inline configuration, whereby the heat transfer is only slightly decreased. It can be shown that the simulations can contribute to optimising complex structures in the future and thus accelerate the development process of new geometries. It can be shown that the development of new heat exchanger pipes is also possible with complex structures, this can be demonstrated here for the first time for structures that can actually be fabricated.